Attributes Of Sorghum Products: "Nasi Bakar and Nasi Bento" Which Affect Consumers among High School - Endang Noerhartati; Diana Puspitasari; Endang Retno Wedowati (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
Understanding consumer product attributes can provide a competitive assessment, exceptionally high school students as young consumers. This study uses a descriptive qualitative approach to obtain broad and in-depth information related to the research objectives. Collecting data using observation, interview, and documentation techniques. Sources of data in this study were 105 high school students on sorghum products: "Nasi Bakar and Nasi Bento" The results showed that 1) the parameters of taste, color, appearance, packaging, and nutritional content were important attributes; 2) consumers value the hierarchical importance of various food attributes; 3) attributes of sorghum products: "Nasi Bakar and Nasi Bento" that affect high school students as young consumers; 4) attributes of a product play an important role as a medium to convey product value to consumers.